NENAD MEMIĆ: RJEČNIK GERMANIZAMA I AUSTRIJACIZAMA U BOSANSKOME JEZIKU: Sarajevo: Connectum, 2014., 285 stranica (ISBN 978-9958-29-059-6). - Puškar, Krunoslav (Slavia Centralis, 2020)
The article presents Rječnik germanizama i austrijacizama u bosanskome jeziku (Dictionary of Germanisms and Austrianisms in Bosnian) by Nenad Memić.
Keywords: Nenad Memić; Dictionary of Germanisms and Austrianisms in Bosnian; review; dictionary; germanisms; Bosnian